2016
DOI: 10.19044/esj.2016.v12n34p24
|View full text |Cite
|
Sign up to set email alerts
|

Variables De Afrontamiento Y Psicológicas Explicativas De La Ansiedad Escénica En Instrumentistas De Viento Metal

Abstract: In the process of musical learning, one of the biggest problems that students must face is stage anxiety. This problem can even lead to the abandonment of studies or lead students to adopt addictive behaviours related to the use of substances to mitigate the harmful consequences that stage anxiety can cause. In this study and taken into account the triple vulnerability system described by Barlow (2000) the presence of higher or lower levels of anxiety is explained from personal characteristics such as helpless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…At ages older than approximately 45–50 years, Fernholz observed a tendency toward lower MPA with increasing age (Fernholz et al, 2019). However, some studies have suggested that the start of musical training is more relevant than age for the development of MPA (Boucher & Ryan, 2011; Zarza-Alzugaray et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At ages older than approximately 45–50 years, Fernholz observed a tendency toward lower MPA with increasing age (Fernholz et al, 2019). However, some studies have suggested that the start of musical training is more relevant than age for the development of MPA (Boucher & Ryan, 2011; Zarza-Alzugaray et al, 2017).…”
mentioning
confidence: 99%
“…In one study, string players and singers reported significantly more MPA than did piano, brass, or woodwind players (Iusca & Dafinoiu, 2012). Zarza-Alzugaray et al (2016, 2017) found that piano and brass students experienced higher levels of MPA in comparison to other music students. However, these results may be associated with differences between primarily solo instruments and those generally played in an orchestra (Casanova et al, 2018).…”
mentioning
confidence: 99%
“…The conductors of youth bands, however, are typically careful to ensure that their leadership styles are different from those typically exercised in adult and professional ensembles (Gustems et al, 2015), and to create a climate of trust and avoidance of reproach. This, together with the prominence of the sound of brass and percussion in each band, could contribute to the building of performers' self-confidence, protect them from psychological vulnerability on stage, and consolidate their own capacity for leadership (Zarza-Alzugaray et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that Music Performance Anxiety (MPA) is a particularization of PA, which is defined as a subjective construct created unconsciously by the musician and that causes a disproportionate reaction to the stimulus presented, in this case, the stage, in any of its forms (Zarza-Alzugaray, 2016). This disproportionate reaction will be considered disadaptive, since it makes it impossible for musicians to perform in front of an audience, also causing harms at physical, cognitive, and behavioural levels, having a direct impact on the overall health (Burin & Osório, 2017).…”
Section: Introductionmentioning
confidence: 99%